Creativity as an Indication of Organizational Performance: - Yasunori Mori (Maketingu rebyu, 2022)
This essay draws on Pierre Bourdieu’s theoretical concepts to examine how an organization’s performance is impacted by the creative activities of employees (organization members). According to the concepts of habitus and field, an individual’s specific way of thinking and acting (i.e. habitus) stems from a commonly shared system within a group, rather than being unique to that individual, but by expressing this disposition (Bourdieu, 1980/1988) and developing specific hobbies, the individual attempts to create their own “field” to differentiate themselves from others (Bourdieu, 1979a/1990; Crossley, 2001/2012; Kataoka, 2019). A regression analysis of a survey of 3,000 consumers (June 2021) found with an accuracy rate of 64.9% that the experience of “performing a musical instrument as a hobby” resulted in a 2.3-fold increase in the sense of accomplishment in one’s job (with results ranging from 1.6-fold to 3.3-fold). While this outcome can be partially explained by factors such as annual household income or the number of books present in the family home at the age of fifteen, these factors had less influence on the outcome compared to hobbies. Age had little explanatory power. This analysis demonstrated that hobbies adopted later in life had relatively more impact than economic capital or cultural capital on class of origin.